Megat Asih: A New Music Composition | Megat Asih: Sebuah Komposisi Musik Baru - Gusti Putu Ngurah Prakrti Mahendra; I Ketut Garwa; Ni Wayan Masyuni Sujayanthi (GHURNITA: Jurnal Seni Karawitan, 2022)
The composition  of the creative percussion entitled Megat Asih is a percussion that has been created with the convenience of the stylist when composing a song, the creation of this creative percussion composition using the literacy of Pande Made Sukerta, makes a creative percussion composition so that with the stages of exploration, improvisation, and forming. Love can come from anywhere, but great love is found in parents, where parents really love their children and give what they want with a positive purpose. A ceremony where a series of religious events exist and are thick with the customs of each region. In this case there is the Ngerorasin ceremony which is a ceremony related to Pitra Yadnya, in the ngeroras ceremony there is a mepegat ceremony, the body of a person who has died/died can no longer be seen by his relatives, making an idea and concept in the composition of Megat asih. Keywords: parents, affection, ceremony, percussion creations.